Efektivitas Model Cycle Learning Menggunakan Media Powerpoint terhadap Hasil Belajar Materi Garis dan Sudut Kelas VII MTsN Karangrejo - Astutik, Santi Dewi; Zahroh, Umy (Jurnal Tadris Matematika, 2018)
The fact that the low quality of learning and mathematics learning outcomes of students because the majority of math teachers still use the method of learning by way of lectures and assignments. In studying mathematics teachers should pay attention to the process of not only prioritize the achievement of learning results seen from UAS only. Therefore, the learning innovation is required. One of the innovative learning models is the Cycle Learning model. The Cycle Learning model is a student-centered learning model that can motivate students when learning, discussing, explaining, and developing. Thus, it can create an active learning atmosphere and not boring. By using media power point learning process becomes more fun. The research pattern used is quantitative approach and type of quasi-experimental research. The sampling technique used is simple random sampling. The sample used 35 experimental group students and 35 students as control group. Data collection methods used are observation, test and documentation. Data analysis technique using Independent Sample T-test. Based on the result of the research, it is concluded that (1) there is significant effect of cyclic learning model using power point toward student learning result of line material and class VII corner of MTsN Karangrejo Tulungagung. This can be seen from the value of t-test obtained of 3.741 is greater than the value of with a level of 5% that is equal to 1.994. (2) Big influence of learning model cycle using power point to student learning result of line material and grade angle VII MTsN Karangrejo Tulungagung. This can be seen from the value obtained manually that is equal to 0.92 in the interpretation table with 82% percentage.